2022
DOI: 10.30541/v49i4iipp.903-923
|View full text |Cite
|
Sign up to set email alerts
|

The State of Food Security in Pakistan: Future Challenges and Coping Strategies

Abstract: Pakistan is a low income developing country. Agriculture is the most important sector of the country meeting food and fibre requirements of the fast growing population. Although the rate of population increase has considerably slowed down from over 3 percent in 1980s to 2.09 percent in 2009-10, it is still considered high.1 With the current rate of population growth, the population is expected to get doubled by 2050—making Pakistan 4th largest nation by 2050 from current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…There is scope for increased yields, as already noted, but there is no evidence to suppose that the rate is likely to increase. To induce an increase in the rate of yield increase would presumably require greater commitment to research, extension and institutional factors such as market (financial) incentives for farmers (Ahmad and Farooq, 2010). Zhu et al (2013) also suggested that increased agricultural research with other adaptations be pursued to reduce the impacts of climate change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is scope for increased yields, as already noted, but there is no evidence to suppose that the rate is likely to increase. To induce an increase in the rate of yield increase would presumably require greater commitment to research, extension and institutional factors such as market (financial) incentives for farmers (Ahmad and Farooq, 2010). Zhu et al (2013) also suggested that increased agricultural research with other adaptations be pursued to reduce the impacts of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The downward revision from 2002 to 2012 with some reversed upward revision to 2015 suggests that there is some uncertainty in projections. Ahmad and Farooq (2010), Bashir et al (2012) and Zulfiqar and Hussain (2014) used population projections consistent with earlier, higher projections, whereas Briscoe Planning Commission (2014) 230 Briscoe and Qamar (2005) 340 Ahmad and Farooq (2010) 340 (in 2045) Bashir et al (2012) c The figures in italics are the described by Zulfiqar and Hussain (2014) as the lower limit and upper limit. and Qamar (2005) (who considered water issues rather than food security) used a projection consistent with more recent lower projections (Table 1).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was the world food crisis of 1972-1974 when the issue of food (in) security attracted colossal attention of the researchers and policy makers. The concept continued to develop and refined overtime and the scholars advanced numerous definitions and voluminous indicators of food security to bring more clarity in the subject [Ahmad and Farooq (2010)]. The most accepted definition of food security is that it is a situation "when all people, at all times, have physical and economic access to sufficient safe and nutritious food to meet their dietary needs and food preferences for a healthy and active life" [FAO (1996)].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The entitlement can be ensured either by own production or having food buying capacity or having access/right to other sources of getting desired food [Timmer (2000); Staaz, et al (2009)]. Only the availability of sufficient food at country/local level does not guarantee that all people are food secure-since low incomes, lack of roads and infrastructure could limit access to desired quantities of quality food [Ahmad and Farooq (2010)]. Therefore, both availability and access parts of food security are inseparably inter-linked [Pinstrup-Andersen (2009)…”
Section: Conceptual Frameworkmentioning
confidence: 99%